Indeks Penulis Volume 31, Tahun 2011 - Indeks Penulis Volume 31, Tahun 2011 (agriTECH, 2011)
Ahmadi, K.G.S. 36, 171Anom, I.D.K. 260Apriyati, E. 46Ariono, D. 242Ariviani, S. 180Arkeman, Y. 60Asnawi, T.M. 368Atmawinata, O. 228